2001
DOI: 10.1093/ndt/16.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and haemodialysis: role of inflammation and duration of dialysis treatment

Abstract: Our results suggest that inflammatory status and duration of dialysis treatment are the most important factors relating to oxidative stress in haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
145
3
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(180 citation statements)
references
References 25 publications
23
145
3
9
Order By: Relevance
“…Outros mais específicos estão associados às consequências da perda de néfrons e levam a distúrbios metabólicos como hiperfibrinogenia, hiperhomocisteinemia e estresse oxidativo. 2 Alguns autores sugerem que a uremia é um estado pró-oxidante, com aumento nos níveis de lipoperoxidação e diminuição da atividade antioxidante. 1,3,4,5 Porém, não está clara a natureza desse estresse oxidativo e se o mesmo é exacerbado pela diálise.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Outros mais específicos estão associados às consequências da perda de néfrons e levam a distúrbios metabólicos como hiperfibrinogenia, hiperhomocisteinemia e estresse oxidativo. 2 Alguns autores sugerem que a uremia é um estado pró-oxidante, com aumento nos níveis de lipoperoxidação e diminuição da atividade antioxidante. 1,3,4,5 Porém, não está clara a natureza desse estresse oxidativo e se o mesmo é exacerbado pela diálise.…”
Section: Introductionunclassified
“…1 universidade de cruz alta (uNIcruZ) 2 universidade Federal do rio Grande do sul 3 Departamento de Medicina Interna da universidade Federal do rio Grande do sul 4 Departamento de Fisiologia, universidade Federal do rio Grande do sul Efeito de uma sessão de hemodiálise sobre o estresse oxidativo sistêmico de pacientes renais crônicos terminais effect of a hemodialysis session on oxidative stress of chronic kidney disease patients…”
unclassified
“…Reduced glutathione (GSH) and oxidized glutathione (GSSG) were simultaneously determined by high-performance liquid chromatography with electrochemical detection as previously described. 34 Briefly, 180 L of homogenate supernatant was mixed with 20 L of 12 mol/L N-acetylcysteine as the internal standard. Separation was performed on a Uptisphere column (ODB, 250 ϫ 4.6 mm, 5 mol/L; Interchim, Montluçon, France) using 10 mmol/L phosphate buffer saline solution, pH 2.7, containing 2% methanol and delivered at a flow rate of 1 mL/min.…”
mentioning
confidence: 99%
“…Our results provide clinical evidence of a significant relationship between decreased circulating klotho levels and increased oxidative stress in ESRD patients. Inflammation is another well-characterized feature of ESRD patients (1,26,31,32), and experimental evidence suggests that klotho modulates inflammation. Zhao et al, using a db/db mouse model of diabetes, showed that klotho negatively regulates the production of NFκB-linked inflammatory cytokines by inhibiting phosphorylation of RelA Ser 536 (12).…”
Section: Discussionmentioning
confidence: 99%